Алхімія в літературі: постановка проблеми - Маркова, Мар’яна; Markova, Maryana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено проблему алхімічного прочитання літературних творів. Спираючись на положення К. Ґ. Юнґа про алхімію як результат експлікації прихованих пластів людської психіки та алхімічну символіку як продукт проекції універсальних образів колективного несвідомого – архетипів, обґрунтовано право¬мірність уключення будь-якого художнього тексту до алхімічного контексту. The article is devoted to the problem of an alchemical reading of the literature. The author raises questions of the etymology of the word «alchemy», its genesis, different approaches to the interpretation of this phenomenon, as well as the problem of interaction between the alchemy and literature. Being based on C. G. Jung’s views on the alchemy as a result of the explication of hidden layers of the human psyche and on the alchemical symbolism as a product of the projection of universal images of the collective unconscious – archetypes, the article justifies the legality of the inclusion of any literary text to the alchemical context. Symbols are qualified in it as the main form of the presence of traces of the author’s unconscious deep substantial layers in the text.
Alchemy in Literature: а Problem
Keywords: алхімія; К. Ґ. Юнґ; література; символ; текст; alchemy; C. G. Jung; literature; symbol; text